Definição de Critérios de Salvaguarda e Valorização da Fábrica de Cerâmica das Devesas - Mariana Silva (2014)
The present article is extracted from an ongoing investigation that aims to define an architectural intervention strategy for the Devesas' Ceramic Factory, leading to its protection and enhancement. The proposed methodology consists on the development of a study focused in four main lines: i) characterization of the it preservation status of the existing, including its historical context; ii) discussion of the definition criteria of the value elements existing in the Portuguese legislation and its application in the context of industrial heritage and in particular to the case study, including the identification of elements of tangible and intangible value; iii) analysis and discussion of case studies , national and international , selected from criteria that can be useful for the particular case study; iv) definition of intervention criteria leading to the establishment of best operational strategy for the protection and enhancement of the remains of the Devesas' Ceramic Factory.